Innovation Potential and Regional Competitiveness studies in the Northern Great Plain region - Németh, Szabolcs (Acta Agraria Debreceniensis, 2012)
1.5 million people live in the large region containing 3 counties, which makes it the second most populated region after Central Hungary. Its economy and land use are still defined by agriculture and it has been the least developed region in the country for a long time. In the country this region has the second lowest GDP per capita and employment rate. In contrast to the low values of the economic indicators the region has high potential for innovation. The University of Debrecen is located in the region having one of the widest range of education and intensive research and development is also a characteristic of the region.